Analysis of Steady-state Characteristics of Thermal Subsystem in Integrated Energy System - Lu QU; Bin OUYANG; Zhichang YUAN; Shuqing ZHANG; Rong ZENG (发电技术)
The integrated energy system (IES) includes various energy forms, complex operation modes, abundant control equipment and coupling links, which brings challenges to its steady-state modeling and steady-state power flow calculation. In order to obtain the steady-state characteristics of the thermal subsystem in the IES, the topological structure of the typical IES was provided; the steady-state models of the power subsystem, the thermal subsystem, the cold subsystem and the distributed energy station were established respectively, and then the hybrid power flow model was established, and the Newton-Raphson algorithm was used to solve the hybrid power flow; the influence of the key technical parameters (including the water supply temperature of the source node, the water outlet temperature of the load node, the length and diameter of the heat network pipe, and the heat load power) on the steady-state power flow of the IES was analyzed. The analysis results can support the planning, design and optimal operation of the IES.